PENGARUH PEMBERIAN PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN MAS KOI (Cyprinus carpio) - Eka Kristina Simamora; Cut Mulyani; Muhammad Fauzan Isma (Fakultas Pertanian Universitas Samudra, 2021)
Koi fish (Cyprinus carpio) is a cultivated commodity that is in great demand by ornamental fish consumen. The research was conducted to determine the effect of different feeding options on the growth and survival of koi fish (Cyprinus carpio). The method used was a completely randomized design with 4 treatments and 3 replications. In P1 namely the use of pellet feed, P2 of artemia feed, P3 of Daphnia sp. feed, and P4 of silk worms. The parameters observed during the study were absolute length growth (PBM), absolute length growth (PPM) , survival rate (SR), and feed conversion ratio (FCR). The result of these observations had a very significant effect on the absolute length growth with the best treatment found at P4 of 2,34 cm, the growth in absolute weight had a very significant effect with the best treatment found at P4 of 3,41 g, and the feed convertion ratio has a very significant effect with the highest treatment found in P3 of 3,11. But it had no significant effect on the survival rate of koi fish (Cyprinus carpio).